2019
DOI: 10.3390/nu11112831
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels in Women with Polycystic Ovary Syndrome: A Population-Based Study

Abstract: Background: Conflicting evidence supports a role for vitamin D in women with reproductive disorders such as polycystic ovary syndrome (PCOS) but studies on large, unselected populations have been lacking. Methods: We conducted a general population-based study from the prospective Northern Finland Birth Cohort 1966 (NFBC1966). Serum 25-hydroksyvitamin D (25(OH)D) levels were evaluated in women with self-reported PCOS (n = 280) versus non-symptomatic controls (n = 1573) at the age of 31 with wide range of endocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 64 publications
0
13
0
2
Order By: Relevance
“…However, in subjects from the AMIGOS trial, no significant association was observed between 25(OH)D deficiency and live births. The study of Lumme et al, which included 1246 women, showed that women with PCOS were no more prone to vitamin D deficiency than non-symptomatic controls, since a considerable number of women in both groups had low 25(OH)D levels with mean 25(OH)D concentrations above the normal range in participants with selfreported PCOS [179]. Nevertheless, the authors of this paper recommend that sufficient vitamin D levels should be ensured in women with PCOS, especially in overweight and obese women.…”
Section: Vitamin D Status and Polycystic Ovary Syndromementioning
confidence: 99%
“…However, in subjects from the AMIGOS trial, no significant association was observed between 25(OH)D deficiency and live births. The study of Lumme et al, which included 1246 women, showed that women with PCOS were no more prone to vitamin D deficiency than non-symptomatic controls, since a considerable number of women in both groups had low 25(OH)D levels with mean 25(OH)D concentrations above the normal range in participants with selfreported PCOS [179]. Nevertheless, the authors of this paper recommend that sufficient vitamin D levels should be ensured in women with PCOS, especially in overweight and obese women.…”
Section: Vitamin D Status and Polycystic Ovary Syndromementioning
confidence: 99%
“…The study population was derived from a prospective, general population-based birth cohort, the Northern Finland Birth Cohort 1966 (NFBC1966). This cohort has been described in detail elsewhere [ 21 , 22 ], including two studies about VitD [ 23 , 24 ]. In this study, we included the cohort participants who attended both the 31-year (1997) and 46-year (2012–2013) clinical follow-ups, before and during NNC launched food fortification programme (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We tested for marital status, physical activity, smoking, alcohol consumption, occupational and education variables and their relevant two-way interactions in the model, but no interaction was found, and their effects did not change the estimates of the other variables in the model. As a sensitivity analysis, we ran a similar regression analysis including the outlier data and an another with exclusion of females using oral contraceptives and hormonal replacement therapy (Online resource 2), since there is evidence for a difference in 25(OH)D among this group [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, even if its nuclear receptor (VDR) is observed in many tissues, including the ovary, the exact mechanism of action of vitamin D has yet to be established in PCOS. Previous trials addressing its circulating levels have shown lower, similar or higher serum concentrations in women with PCOS (12,(14)(15)(16).…”
Section: Polycystic Ovary Syndrome: New Insights On the Puzzle Of Adimentioning
confidence: 98%
“…In another recent study addressing the prevalence of vitamin D deficiency in women with PCOS and different phenotypes, those presenting androgen excess had higher crude odds ratio for vitamin D deficiency, but the significance was lost after adjustment for BMI and ethnicity (18). Indeed, considering that obesity has been linked to lower serum vitamin D levels (19) and women with PCOS present higher prevalence of overweight/obesity as well as insulin resistance, assessing a potential independent role of vitamin D in PCOS still remains a challenge (14).…”
Section: Polycystic Ovary Syndrome: New Insights On the Puzzle Of Adimentioning
confidence: 99%